Excellence and Lasting Achievement of Excellent Results (Journal of Universal Excellence, 2026)
Research Question (RQ): How do organizations achieve excellent results on an ongoing basis?Purpose: The purpose is to find out with what approach in the organization they achieve the permanent achievement of excellent results. What methods and approaches do they use for this.Method: A qualitative method was used for analysis. Review of literature from various Internet titles, articles, brochures, master's theses.Results: In order to achieve permanently excellent results, it is necessary to include all employees, as well as all factors according to the EFQM model.Organization: The leadership of the organization and the related vision, values and strategy are especially important for the lasting achievement of lasting excellent results.Society: An An organization that permanently achieves excellent results must ensure that its operations do not harm the environment through their operations and are sustainable.Originality: Organizations follow the EFQM model, using the Radar tool to analyze data.Limitations/Future Research: The research could be extended to other building blocks and described for our organization.
Keywords: excellent results; EFQM excellence model; EFQM model; clients; RADAR tool; mission; sustainability; leadership; vision; values; employees